PENGARUH PENGUASAAN HUKUM II NEWTON TERHADAP HASIL BELAJAR FISIKA SISWA PADA MATERI POKOK MOMENTUM DI SMA NEGERI SAIPAR DOLOK HOLE - Mutiara Siagian (JURNAL PhysEdu (PHYSICS EDUCATION), 2022)
This research aims to know whether there is significant effect of Newton II law mastery to students’ achievement in momentum of the XI grade students of SMA Negeri 1 Saipar Dolok Hole. The population of this research is all of XI grade students of SMA Negeri 1 Saipar Dolok Hole, consist of 2 classes, it is 75 students. Sample of this research is 35 students, taken by using cluster sampling. The data was analyzed by two steps, the first step by descriptive analysis to see the description of both variables, and the second step by using inferential analysis by using . Based on the calculation, the mean of the Students’ Newton II law mastery is 70,60. It is good category. Then the mean of the students’ achievement in momentum is 67,60. It is enough category. Based on the calculation in inferential analysis, it is found that is 47,47 and if it is compared to in 5% significant, it is found 1,69. After comparing and , it is got that is greater than (47,47 > 1,69). The hypothesis is accepted. Means that there is significant effect of Newton II law mastery to students’ achievement in momentum of the XI grade students of SMA Negeri 1 Saipar Dolok Hole.